Hubungan Ketersediaan Sarana Sanitasi Dasar dan (PHBS) dengan Kejadian Diare Balita di Puskesmas Tanah Pasir Aceh Utara - Elvieta, Elvieta; Ernita, Ernita (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2024)
Diarrhea is a leading cause of suffering and mortality among children, accounting for approximately 9% of all deaths of children under the age of 5 worldwide in 2021. This study aims to determine the relationship between the availability of basic sanitation facilities (clean water facilities and toilet conditions) and Clean and Healthy Living Behavior (PHBS) with the incidence of diarrhea in toddlers at Puskesmas Tanah Pasir, North Aceh Regency, in 2024. This research employs a descriptive-analytic method with a cross-sectional design, involving 95 mothers with toddlers. The sample was taken using purposive sampling, and data were collected through questionnaires and interviews. The results show that the availability of clean water facilities has a significant relationship with the incidence of diarrhea in toddlers (p value = 0,005), toilet conditions also have a significant relationship with the incidence of diarrhea in toddlers (p value = 0,000), and PHBS behavior is significantly related to the incidence of diarrhea in toddlers (p value = 0,003). It is recommended that health workers enhance collaboration with cross-sector stakeholders and conduct continuous education and outreach programs.